Evaluating Plastic Waste Management Strategies: Logistic Regression Insights on Pyrolysis vs. Recycling - Dimitrios-Aristotelis Koumpakis; Christos Vlachokostas; Apostolos Tsakirakis; Savvas Petridis (Recycling)
The global plastic production total has risen to more than 400 million tons per year; this number is mainly driven by industrial appliances. In the EU, where the annual production is about 30 million tons, only 32% of plastic waste is recycled. Therefore, a need for a robust and efficient waste management strategy has emerged. This study will introduce a novel logistic regression-based decision-making framework that focuses on the environment and the economy while also considering energy intensity and logistics. These factors reflect the use of Life Cycle Assessment (LCA) in this study, which is an approach that determines the selection of waste management strategies across different European countries. This study introduces a model with 94% sensitivity and 97% overall accuracy in order to compare pyrolysis and plastic waste recycling management methods. One of the main findings is the fact that pyrolysis demonstrated a maximum conversion efficiency of 88%; in comparison, the conversion efficiency for recycling was approximately 58%. Pyrolysis also generates by-products, such as syngas and pyrolytic oil, which are valuable. To conclude, this study is a tool for policymakers and industry leaders, so that they can make sustainable waste management decisions with data-driven and evidence-based reasoning.